Green Banking and Corporate Sustainability Performance In Indonesian Banking Sector - Aliffianti Safiria Ayu Ditta (Proceeding International Conference on Digital Education and Social Science, 2024)
This study aims to determine the implementation of green banking on the sustainability performance of the Indonesian banking sector. Green banking in this study will be proxied with green product, green operational, and green policy indicators, while the company’s sustainable performance will be proxied with multiple bottom line indicators, namely economic, environmental, ethic, social and governance (EEESG). Regression test are used to see how green banking affects a company’s sustainable performance. The results indicate that green policy affects all aspects of the company’s sustainable performance. Management policies that seek to synergize economic, environmental, etchical, social and governance aspects can encourage companies to achieve sustainable performance. This study recommends the concept of Green banking as one of the strategies, policies and procedures in meeting the demand of OJK regulation Number 51/POJK.03/2017 concerning the application of sustainable finance for financial service institutions, issuers and public companies.